Real-World Safety, Effectiveness, and Patient-Reported Outcomes in Patients with Chronic Hepatitis C Virus Infection Treated with Glecaprevir/Pibrentasvir: Updated Data from the German Hepatitis C-Registry (DHC-R) - Markus Cornberg; Albrecht Stoehr; Uwe Naumann; Gerlinde Teuber; Hartwig Klinker; Thomas Lutz; Hjördis Möller; Dennis Hidde; Kristina Lohmann; Karl-Georg Simon (Viruses, 2022)
Using data from the German Hepatitis C-Registry (Deutsche Hepatitis C-Register, DHC-R), we report the real-world safety and effectiveness of glecaprevir/pibrentasvir (GLE/PIB) treatment and its impact on patient-reported outcomes (PROs) in underserved populations who are not typically included in clinical trials, yet who will be crucial for achieving hepatitis C virus (HCV) elimination. The DHC-R is an ongoing, non-interventional, multicenter, prospective, observational cohort study on patients treated for chronic HCV infection in Germany. The data cutoff was 17 January 2021. The primary effectiveness endpoint was sustained virologic response at post-treatment Week 12 (SVR12). Safety outcomes were assessed in all patients receiving GLE/PIB. PROs were assessed using the SF-36 survey. Of 2354 patients, 1964 had valid SVR12 data (intention-to-treat analysis). Of these, 1905 (97.0%) achieved SVR12 with rates similar across the comorbidities analyzed, except for people who actively use drugs (PWUD (active)) (86.4%). Excluding those who discontinued treatment and did not achieve SVR12, or were reinfected with HCV, the rate was 99.3%, with similar results regardless of comorbidity. PWUD (active) and those with psychiatric disorders had the most meaningful improvements in PROs. Adverse events (AEs) occurred in 631/2354 patients (26.8%), and serious AEs in 44 patients (1.9%). GLE/PIB was highly effective and well tolerated in this real-world study of patient groups key to HCV elimination.